Availability of equipment and medications for non-communicable diseases and injuries at public first-referral level hospitals: A cross-sectional analysis of service provision assessments in eight low-income countries - Gupta, Neil; Coates, Matthew M; Bekele, Abebe; Dupuy, Roodney; Fénelon, Darius Leopold; Gage, Anna D; Getachew, Theodros; Karmacharya, Biraj Man; Kwan, Gene F; Lulebo, Aimée M; Masiye, Jones K; Mayige, Mary Theodory; et al. (BMJ Journals, 2022)
This article was published in BMJ Open by BMJ Journals [© Author(s) (or their employer(s)) 2020. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.] and the definite version is available at: https://doi.org/10.1136/bmjopen-2020-038842 The Journal's website is at: https://bmjopen.bmj.com/content/10/10/e038842